Branding, Product Quality and Marketing Strategy on Purchasing Decisions in the Batik Creative Industry (Case Study of Pati Batik UMKM Centers) - Ria - Dinata; Nur - Rini; Karnowahadi - Karnowahadi (Politeknik Negeri Semarang, 2022)
This study aims to analyze the effect of Product Branding, Product Quality and Marketing Strategy on Purchasing Decisions on the Batik Creative Industry (Case Study at the Batik MSME Center in Pati Regency). This study uses quantitative research methods with convenience sampling techniques. Convenience Sampling is a way of choosing who is suitable by chance found by researchers who are seen as data sources by distributing questionnaires to consumers of batik SMEs in Pati Regency as many as 100 respondents. The data analysis method used is a test technique, with SPSS 26 statistical test tool. It is found that partially product branding has no significant effect on purchasing decisions, product quality partially has a positive and significant effect on purchasing decisions, and partially marketing strategy has a positive effect. and significant on purchasing decisions. Together, product branding, product quality and marketing strategy have a positive and significant effect on purchasing decisions. The magnitude of the coefficient of determination is 0.407, this means that 40.7% of purchasing decisions can be explained by product branding, product quality and marketing strategy, while the remaining 59.3% is explained by other variables not examined in this study. It is recommended to maintain good product branding, optimize product quality and marketing strategies to improve purchasing decisions